Dinamika Perkembangan Kosakata Bahasa Indonesia Ditinjau dari Aspek Pemaknaan Jurnal Sosioteknologi Edisi 23 Tahun 10, Agustus 2011 1117 DINAMIKA PERKEMBANGAN KOSAKATA BAHASA INDONESIA DITINJAU DARI ASPEK PEMAKNAAN - Nani Darheni (Jurnal Sosioteknologi, 2011)
Languages have evolved in line with the development taking place within the community of native speakers. The development of science, technology, and culture makes language also evolved to meet the demands of development. The rapid development of science and technology in the Western world, for example, has had an impact on the development of the Indonesian language. Multilingual society, such as the Indonesian people, sooner or later, will get acquainted with other languages that are definitely not the original language. This happens also in the development of our national language, Indonesian language, which at any time continues to grow. This development can be influenced by various factors of migration, housing, education, and others. It may affect the expansion of vocabulary or the meaning of vocabulary in the form of expansion or narrowing of the meaning of the word division. In addition to the expansion of meaning and a narrowing of meaning, the meaning changes are considered by Indonesian as the efforts to revive the archaic lexical items with the same meaning, new significance with the expansion of meaning or new meaning. Therefore, expansion or extension of the meaning of words, narrowing the meaning of the word, and change the meaning of words affect change in Indonesian word meaning emerging today, besides archaic revival of lexical items. This study describes changes in Indonesian vocabulary based on aspects of its meaning. Indonesian vocabulary has experienced dynamic development and expansion of the meaning of language change (extension of meaning), a narrowing of meaning, pejoration, amelioration, synesthesia, and associations. Keywords: dynamics of vocabulary, meaning, the Indonesian language